COMPLEX KARYOTYPE IN CHRONIC LYMPHOCYTIC LEUKEMIA – REVIEW ARTICLE - Antić, Darko; Kozarac, Sofija; Tomic Vujovic, Kristina; Otasevic, Vladimir; Pesic, Andrej; Vukovic, Vojin; Mihaljevic, Biljana (Medical Research, 2023)
Chronic lymphocytic leukemia (CLL) is a genetically heterogeneous disease with chromosomal and genomic aberrations found in more than 80% of patients, either by conventional or by molecular cytogenetics. Complex karyotype (CK) is defined as the presence of ≥ 3 structural or numerical aberrations in the same clone of CLL malignant cell and is considered a potential prognostic parameter in CLL. The detection of CK in CLL patients can potentially affect prognosis and treatment, considering that CK is associated with the progression of HLL and a worse prognosis, as well as with a higher risk of developing Richter transformation. This review will assess the complexity of karyotype analysis in CLL and its prognostic importance and implications.